Influence of blood flow occlusion on the development of peripheral and central fatigue during small muscle mass handgrip exercise. (2nd August 2015) - Broxterman, R. M.; Craig, J. C.; Smith, J. R.; Wilcox, S. L.; Jia, C.; Warren, S.; Barstow, T. J.
Abstract : Key points: Critical power represents an important threshold for neuromuscular fatigue development and may, therefore, dictate intensities for which exercise tolerance is determined by the magnitude of fatigue accrued. Peripheral fatigue appears to be constant across O2 delivery conditions for large muscle mass exercise, but this consistency is equivocal for smaller muscle mass exercise. We sought to determine the influence of blood flow occlusion during handgrip exercise on neuromuscular fatigue development and to examine the relationship between neuromuscular fatigue development and W ′. Blood flow occlusion influenced the development of both peripheral and central fatigue, thus providing further evidence that the magnitude of peripheral fatigue is not constant across O2 delivery conditions for small muscle mass exercise. W ′ appears to be related to the magnitude of fatigue accrued during exercise, which may explain the reported consistency of intramuscular metabolic perturbations and work performed for severe‐intensity exercise. Abstract: The influence of the muscle metabolic milieu on peripheral and central fatigue is currently unclear. Moreover, the relationships between peripheral and central fatigue and the curvature constant ( W ′) have not been investigated. Six men (age: 25 ± 4 years, body mass: 82 ± 10 kg, height: 179 ± 4 cm) completed four constant power handgrip tests to exhaustion under conditions of control exercise (Con), blood flow occlusion exercise (Occ), Con with 5 min post‐exercise blood flow occlusion (Con + Occ), and Occ with 5 min post‐exercise blood flow occlusion (Occ + Occ). Neuromuscular fatigue measurements and W ′ were obtained for each subject. Each trial resulted in significant peripheral and central fatigue. Significantly greater peripheral (79.7 ± 5.1% vs . 22.7 ± 6.0%) and central (42.6 ± 3.9% vs . 4.9 ± 2.0%) fatigue occurred for Occ than for Con. In addition, significantly greater peripheral (83.0 ± 4.2% vs . 69.0 ± 6.2%) and central (65.5 ± 14.6% vs . 18.6 ± 4.1%) fatigue occurred for Occ + Occ than for Con + Occ. W ′ was significantly related to the magnitude of global ( r = 0.91) and peripheral ( r = 0.83) fatigue. The current findings demonstrate that blood flow occlusion exacerbated the development of both peripheral and central fatigue and that post‐exercise blood flow occlusion prevented the recovery of both peripheral and central fatigue. Moreover, the current findings suggest that W ′ may be determined by the magnitude of fatigue accrued during exercise. Abstract :